A festa de casamento contemporânea como ritual de consumo e da memória: uma análise das imagens da festa no Instagram - Lira, Penélope Maria Melo e (2015)
The work objective was to investigate the consumption material, symbolic and affective present in the wedding party, and to recognize the consumer goods such as social and ritual this time exposed on Instagram markers, understanding the wedding party as a privileged space of consumption and memory. This is a qualitative research whose research instruments were the literature, the main theoretical frameworks work of Douglas and Isherwood, understanding the consumer as ritual; Rose Rocha, on consumer images and still articulated the concept of memory culture, ritual and celebration, through the work of Yuri Lotman, of Jerusha Ferreira, Monica Nunes, Ecléa Bosi, among other authors that link the interconnection of memory autobiographical and cultural; documentary research, which consisted of the removal of the wedding party photos on Instagram. Two brides Instagram users were chosen by purposive sampling, because they have in their profiles significant amounts of pictures of the wedding party to be analyzed, exposing the various wedding ritual steps on Instagram and other festivities that are part of it. By studying the images, it was observed that the brides memories bolster a logic of consumption, in which the goods and objects contribute to this joint. It was possible to conclude that the images shared by brides can reveal aspects of a symbolic consumption and equipment belonging to the party and, likewise, update the circulation of this text memory of culture.